Pola Permainan Alat Musik Keroncong dan Tenor di Orkes Keroncong Irama Jakarta - Hery Supiarza; Deni Setiawan; Cece Sobarna (Institut Seni Indonesia Yogyakarta, 2019)
Penelitian ini mendiskusikan pola permainan alat musik keroncong dan tenor serta penerapannya pada lagu “Cente Manis” dan “Sambel Cobek”. Kedua alat musik ini merupakan identitas keroncong gaya Jakarta. Penelitian dilakukan dengan pendekatan kualitatif deskriptif dan data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Berdasarkan hasil penelitian ditemukan bahwa asal mula istilah alat musik keroncong berasal dari bunyi alat musik itu sendiri. Istilah tenor merujuk pada istilah suara laki-laki tertinggi. Ditemukan juga teknik permainan alat musik keroncong dan tenor yaitu teknik rasguaedo (prung), strumming, arpeggio dan dengan cara dipetik satu-satu pada setiap senar. Teknik memainkan alat musik keroncong dan tenor tersebut meliputi pola permainan dobel engkel, dobel balik, format dan gaya lama. Permainan keempat pola tersebut bergantung pada lagu yang akan dibawakan dan kesepakatan para personilnya. The Approach of Orff-Schulwerk for Prospective Music Teachers in Kindergarten Schools. The topic in this article focuses on the application of Orff-schulwerk for university students as prospective teachers in school, including kindergarten. Orff-schulwerk can be seen as an approach to music education. In related to primary education, this approach focuses on the children needs and develops children musicality through necessary activities (elemental) in music and movement. Some questions in this article are: 1) what kind of Orff-schulwerk that can be used by prospective teachers in the learning process at kindergarten? 2) what benefits can be obtained by teacher candidates through the application of the Orff-schulwerk approach? And 3) how do prospective teachers who use this approach can understand their role in learning? The method used in this study is action research. The findings in this research are prospective teachers understand that: 1) Orff-schulwerk can be used in related to exploration – imagination – creation that involving music and movement; 2) this approach is useful for developing student musicality in the learning process in kindergarten; and 3) in this approach, prospective teachers are acted as facilitators who can create an atmosphere of learning that stimulate students’ imagination and creation. This study concludes that the Orff-schulwerk approach should be mastered by prospective teachers who teach in schools, including kindergarten. By having an understanding of this approach, both theoretically and practically, prospective teachers not only enhance their knowledge but also support the national education goals, namely the students’ character building in schools.Keywords: Orff-Schulwerk; music education; kindergarten teachers